Prevalence of and progression to abnormal noninvasive markers of liver disease (aspartate aminotransferase-to-platelet ratio index and Fibrosis-4) among US HIV-infected youth. (27th March 2016) - Kapogiannis, Bill G.; Leister, Erin; Siberry, George K.; Van Dyke, Russell B.; Rudy, Bret; Flynn, Patricia; Williams, Paige L.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: To longitudinally characterize noninvasive markers of liver disease in HIV-infected youth. Design: HIV infection, without viral hepatitis coinfection, may contribute to liver disease. Noninvasive markers of liver disease [FIB-4 (Fibrosis-4) and APRI (aspartate aminotransferase-to-platelet ratio index)] have been evaluated in adults with concomitant HIV and hepatitis C, but are less studied in children. Methods: In prospective cohorts of HIV-infected and HIV-uninfected youth, we used linear regression models to compare log-transformed FIB-4 and APRI measures by HIV status based on a single visit at ages 15–20 years. We also longitudinally modeled trends in these measures in HIV-infected youth with two or more visits to compare those with behavioral vs. perinatal HIV infection (PHIV) using mixed effect linear regression, adjusting for age, sex, body mass index, and race/ethnicity. Results: Of 1785 participants, 41% were men, 57% black non-Hispanic, and 27% Hispanic. More HIV-infected than uninfected youth had an APRI score more than 0.5 (13 vs. 3%, P  < 0.001). Among 1307 HIV-infected participants with longitudinal measures, FIB-4 scores increased 6% per year ( P  < 0.001) among all HIV-infected youth, whereas APRI scores increased 2% per year ( P  = 0.007) only among PHIV youth. The incidence rates (95% confidence interval) of progression of APRI to more than 0.5 and more than 1.5 were 7.5 (6.5–8.7) and 1.4 (1.0–1.9) cases per 100 person-years of follow-up, respectively. The incidence of progression of FIB-4 to more than 1.5 and more than 3.25 were 1.6 (1.2–2.2) and 0.3 (0.2–0.6) cases per 100 person-years, respectively. Conclusion: APRI and FIB-4 scores were higher among HIV-infected youth. Progression to scores suggesting subclinical fibrosis or worse was common.